2006
DOI: 10.1038/nature05162
|View full text |Cite
|
Sign up to set email alerts
|

Identification of nesfatin-1 as a satiety molecule in the hypothalamus

Abstract: The brain hypothalamus contains certain secreted molecules that are important in regulating feeding behaviour. Here we show that nesfatin, corresponding to NEFA/nucleobindin2 (NUCB2), a secreted protein of unknown function, is expressed in the appetite-control hypothalamic nuclei in rats. Intracerebroventricular (i.c.v.) injection of NUCB2 reduces feeding. Rat cerebrospinal fluid contains nesfatin-1, an amino-terminal fragment derived from NUCB2, and its expression is decreased in the hypothalamic paraventricu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

28
781
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 866 publications
(837 citation statements)
references
References 23 publications
28
781
0
4
Order By: Relevance
“…Indeed, by the generation of specific antibodies and implementation of immunohistochemical (IHC) analyses and immunoassays, nesfatin-1 was shown to be produced in the hypothalamus and present in the cerebrospinal fluid (index of this being a secreted neuropeptide). Co-localization of nesfatin-1 and PC3/1 and PC2 suggested that the latter are involved in the cleavage of nesfatin-1 from the NUCB2 precursor (Oh et al 2006). …”
Section: Identification and Structural Biology Of Nesfatin-1mentioning
confidence: 99%
See 4 more Smart Citations
“…Indeed, by the generation of specific antibodies and implementation of immunohistochemical (IHC) analyses and immunoassays, nesfatin-1 was shown to be produced in the hypothalamus and present in the cerebrospinal fluid (index of this being a secreted neuropeptide). Co-localization of nesfatin-1 and PC3/1 and PC2 suggested that the latter are involved in the cleavage of nesfatin-1 from the NUCB2 precursor (Oh et al 2006). …”
Section: Identification and Structural Biology Of Nesfatin-1mentioning
confidence: 99%
“…Among the clones identified to be regulated by PPAR-g, one was highlighted as i) having a signal peptide (index of secreted proteins), ii) being produced by neuronal-(medulloblastoma HTB185) and adipocyte-(3T3-L1) derived cell lines, and iii) displaying profound stimulated expression following troglitazone (Oh et al 2006). This target was shown to correspond to the gene encoding nucleobindin 2 (NUCB2), also termed NEFA (for DNA binding/EF-hand/acidic protein).…”
Section: Identification and Structural Biology Of Nesfatin-1mentioning
confidence: 99%
See 3 more Smart Citations